Hakikat Dan Teori Pengetahuan Dalam Konteks Pendidikan Islam: ( Teori Akal Dan Teori Panca Indra) - Megawati Fajrin (AL -ALLAM, 2020)
"Knowledge will never end, until hearing, sight and human heart still function optimally, it will give birth to new knowledge. Epistemology or philosophy of knowledge is basically also a rational effort to weigh and determine the cognitive value of human experience in its interaction with oneself, the social environment, and the natural surroundings. So epistemology is a discipline that is evaluative, normative, and critical.